Student Learning Difficulty Problems In Islamic Counseling Perspective And Solutions To Handling At Islamic Senior High School (MAPN) 4 Medan - Solihah Titin Sumanti, Dina Aulia (LPPPIPublishing, 2021)
The purpose of this study is to analyze what types of learning difficulties are faced by students, implementation solutions for handling student learning difficulties in the perspective of Islamic counseling, obstacles from solutions to handling students' learning difficulties in the perspective of Islamic counseling, and the efforts made in overcoming difficulties in handling difficulties. student learning in the perspective of Islamic counseling. This research method is to use a phenomenological qualitative research method, which is to reveal the problems that occur to find and understand what is hidden behind the problems that occur. Research implementation Qualitative phenomenology is aiming to understand and interpret the various problems that exist. The result of this research is the difficulty learning that experienced by students in Senior High School 4 Terrain is difficult to understand the eye subjects specified as subjects of mathematics and physics so that the results of learning low. Students work to help the elderly that causes the activity of learning the students there are disturbed Students experience fatigue from working too much to help their parents in certain endeavors. Students are bored with learning because there are too many assignments given from school, especially subject assignments given by teachers at school. Solution problems of difficulty of learning of students in the perspective of counseling Islami which provides guidance with techniques conventional ie conduct meetings directly with the students, and then perform the stages of identifying problems.